SIMULASI KERUNTUHAN BENDUNGAN BILI-BILI KABUPATEN GOWA PROVINSI SULAWESI SELATAN - Irpan Chumaedi; rustan; Linda Handayani (JOURNAL ONLINE OF PHYSICS, 2019)
The extreme weather that occurred on January 22-24, 2019 in the Makassar city and surrounding areas caused massive flooding in the downstream area of ​​the Bili-Bili DAM which covered 5 districts and cities, namely Gowa Regency, Makassar City, Jeneponto Regency, Maros Regency, and Selayar Regency. There 6757 people were displaced and tens of hectares of rice fields and housing were inundated. As a form of evaluation in the context of disaster mitigation efforts if similar or larger events occur in the future, it is very important to do a floods simulation to mapping which areas will be affected by flood inundation if the Bili-Bili DAM collapses. The software used to simulate flooding in this study is HEC-RAS 2D. The object of research is focused in the city of Makassar which is a densely populated city center and other vital objects. The parameters analyzed are the distribution of flood inundation area and the depth of flood inundation. Simulation results that have been calibrated will be used as a reference for disaster mitigation planning.